The Narrative Pattern of Inquiry. The New Philosophy of History in the Light of John Dewey’s Pragmatism - Tozzi Thompson, Verónica; Penelas, Federico (Analysis. Journal of Philosophical Research, 2022)
Dewey’s thoughts on historical knowledge should be appreciated under the light of the disputes in contemporary philosophy of history, especially in the narrative drift. On the one hand, as he addresses the subject in terms of narration and writing, this chapter appears as a precursor text of narrativist philosophy of history. Furthermore, given that his accounts on history are framed within a general theory of inquiry (narrative writing of the past is a case of judgment), offers us a useful tool to avoid skeptical readings of narrativism. We find in Deweyan text a strong strategy to give good reasons (in terms of pragmatist rationality) to appeal to literary studies when analyzing the processes of construction and acceptance of historical knowledge. Finally, as he presents narrative as the expression of the temporal phase of inquiry in general, on the one hand, he avoids engaging with the methodological dualism that stablishes substantive differences between history and science, and, on the other, he gives arguments against the collapse between history and artistic literature. However, they will not be expressed in Rankean terms (something that Dewey explicitly rejected) but in pragmatist terms, that is, pointing out a functional difference between historical and artistic narrative.